Overview of tuberculosis case in Sukoharjo Regency 2017-2021 - Yusti Fitya Lutfana; Noor Alis Setiyadi (Nur Science Institute, 2024)
Tuberculosis (TB) remains a major public health problem in Indonesia, including in Sukoharjo Regency, which shows year-to-year changes in the number of cases. This study aims to describe TB cases in Sukoharjo Regency during the 2017–2021 period. The study used a descriptive design utilizing secondary data from TB case reports from 12 community health centers and reported to the Sukoharjo Regency Health Office. Data were analyzed descriptively to describe the number of suspected, confirmed, treated, and recovered cases. The results showed that the number of TB cases fluctuated during the study period, with the highest number of cases occurring in 2019 and the lowest in 2020. Variations in the number of cases were influenced by individual factors, environmental factors, and the implementation of TB screening and examination programs. In addition, obstacles were still found in treatment that could potentially lead to recurrent cases, discontinuation of treatment, therapy failure, and drug resistance. Therefore, evaluation and strengthening of TB control programs are necessary to support the achievement of the 2030 tuberculosis elimination target.